Analisis Kebutuhan Pelatihan Karyawan Divisi Perbengkelan di Perusahaan Komponen Otomotif Bahan Karet - Abidi, Aulia Rizqi Nur; Pandjaitan, Nurmala K; Affandi, Joko (Institut Pertanian Bogor, 2017)
OBK is the company's acquisition in 2013. This acquisition led to a change in the managerial rank that influence new policies were implemented company. New policy of employee development as an effort to increase the performance of the company. This study aimed to analyze the perception of Workshop division employee of accomplished trainings at OBK Company and their improved performance after the training. This study analyze the relationship between the respondents perceptions towards accomplished training activities and the perceptions towards performance after the training. The perception data were processed using an average test score, the correlation using Pearson’s rank test and training Need Assessment Tool (TNA-T) to analyze the employee training needed. The results showed that the perception of production and PPIC subdivisions are satisfied with the training organized by the company and the perception of Maintenance and QC subdivision are quite satisfied. Perception on the improved performance of Production, QC and PPIC subdivisions after the training is increased on the average. Meanwhile the performance of Maintenance subdivision is enough. The relationship between the variables of training and improved performance in Production, PPIC, QC and Maintenance subdivision has a positive direction. This shows that the higher the perception of the training, the higher the perception of improved performance. A strong and significant relationship between training and improved performance are on Production, QC and PPIC subdivisions. Respondent perceptions on these subdivisions are high on the average. On the Maintenance subdivision, the relationship is low and not significant between training and performance. Low relationship is assumed to occur because the assessments of respondents tend to vary on the training variable. The result of TNA tools that training is required by all respondents but not urgent.